Coronavirus disease 2019: features of comprehensive cardiac and pulmonary rehabilitation - M. G. Bubnova; E. V. Shlyakhto; D. M. Aronov; A. S. Belevsky; M. Yu. Gerasimenko; M. G. Glezer; M. N. Gordeev; O. M. Drapkina; G. E. Ivanova; D. G. Ioseliani; N. S. Karamnova; E. D. Kosmacheva; et al. (Российский кардиологический журнал)
The expert consensus of the Russian communities discusses the issues of comprehensive medical rehabilitation of patients with coronavirus disease 2019 (COVID-19). COVID-19 is a contagious infectious disease that can cause pulmonary, cardiac, motor, metabolic, neurocognitive and mental disorders, that is, multiple organ dysfunction. COVID-19 survivors, especially after a severe clinical course, face serious psychological and physical problems, posttraumatic stress, cognitive dysfunction, nutritional deficiencies and exacerbation of concomitant chronic diseases. Some patients, regardless of the COVID-19 severity, have a long clinical course of the disease (“chronic-COVID”, “long COVID”). There is evidence of post-acute COVID-19 syndrome. In this regard, patients after COVID-19 will need rehabilitation measures. The expert consensus of the Russian communities presents general principles, stages and aspects of medical rehabilitation after COVID-19, indications and contraindications for rehabilitation interventions. The paper includes recommendations on comprehensive cardiac and pulmonary rehabilitation, as well as specifics of rehabilitation care for different COVID-19 courses within the national three-stage rehabilitation system.